Antiferromagnetic Phase Transition in Cr2As via Anisotropy of Exchange Interactions - V. I. Valkov; A. V. Golovchan; Upali Aparajita; Oleksiy Roslyak (Advances in Materials Science and Engineering)
The electronic structure of antiferromagnetic Cr2As is investigated. Anisotropy of exchange interactions between chrome sublattices is determined JXCrI−CrII=4.77 meV,JYCrI−CrII=−6.36 meV. The behavior of exchange integrals from the magnetic structure is analyzed.